2015
DOI: 10.1007/s00432-015-2054-7
|View full text |Cite
|
Sign up to set email alerts
|

TH and DCX mRNAs in peripheral blood and bone marrow predict outcome in metastatic neuroblastoma patients

Abstract: TH and DCX mRNAs levels in PB and BM assessed by RT-qPCR should be considered in new pre-treatment risk stratification strategies to reliable estimate outcome differences in metastatic NB patients. In those high-risk metastatic NB, TH and DCX mRNA quantification could be used for the assessment of response to treatment and for early detection of progressive disease or relapses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 25 publications
1
30
0
Order By: Relevance
“…Importantly, to provide sufficient follow-up data, the analy- Many studies have explored potential methods of identifying HR-NBL patients with particularly poor outcomes. These include quantification of tumour-related mRNA in blood or BM samples, 10,26,27 semi-quantitative scoring of mIBG response, 8,9,28 identification of specific tumour genetic aberrations such as ALK mutation or TERT rearrangements [29][30][31] and multiple different gene expression classifiers. [32][33][34] As yet, these techniques have not yet been simultaneously evaluated in sufficiently large homogeneously treated HR-NBL patient populations.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, to provide sufficient follow-up data, the analy- Many studies have explored potential methods of identifying HR-NBL patients with particularly poor outcomes. These include quantification of tumour-related mRNA in blood or BM samples, 10,26,27 semi-quantitative scoring of mIBG response, 8,9,28 identification of specific tumour genetic aberrations such as ALK mutation or TERT rearrangements [29][30][31] and multiple different gene expression classifiers. [32][33][34] As yet, these techniques have not yet been simultaneously evaluated in sufficiently large homogeneously treated HR-NBL patient populations.…”
Section: Discussionmentioning
confidence: 99%
“…Yanez et al reported high levels of DCX mRNA detection by RT-qPCR in the PB and BM at diagnosis. According to them, high levels of DCX in BM independently predicted poor event-free survival and overall survival in NB patients (Yanez et al, 2016). They consequently suggested that DCX mRNA levels in PB and BM assessed by RT-qPCR may be considered in new pretreatment risk stratification strategies to reliably estimate outcome differences in metastatic NB patients.…”
Section: Dynamic Involvement Of DCX In Cancersmentioning
confidence: 99%
“…Freezing testicular tissue allows subsequent transplantation either by infusion of a testicular cell suspension into the seminiferous tubules (26) or intra-testicular grafting of tissue (27). However, >60% of children with metastatic NB have circulating tumor cells at the time of diagnosis (28). Although testis is not the most frequent NB invasion site, numerous cases of testicular NB metastasis have been described previously.…”
Section: Discussionmentioning
confidence: 99%